2022
DOI: 10.1186/s12987-022-00314-2
|View full text |Cite
|
Sign up to set email alerts
|

Brain barriers virtual: an interim solution or future opportunity?

Abstract: Background Scientific conferences are vital communication events for scientists in academia, industry, and government agencies. In the brain barriers research field, several international conferences exist that allow researchers to present data, share knowledge, and discuss novel ideas and concepts. These meetings are critical platforms for researchers to connect and exchange breakthrough findings on a regular basis. Due to the worldwide COVID-19 pandemic, all in-person meetings were canceled i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…60,61,68,71,79,81,94 This was attributed to improved attendance, greater accessibility, and decreased environmental impact. Of the remaining publications, 3 of 12 did not specifically ask the participants about format preference, although respondents indicated that they had enjoyed the conference and were willing to continue meeting virtually; 42, 89,96 1 of 12 reported a majority preference for in-person meetings; 44 and the final study reported approximately equal preference for in-person and hybrid/virtual. 82 Some studies attempted to evaluate conference impact using objective metrics -such as examining links between attendance and performance on the American Board of Emergency Medicine In-Training Examination and U.S. Medical Licensing Examination, 39 or distributing case study questionnaires to conference participants and non-participants to determine "whether the diagnostic and therapeutic choices of program participants were consistent with evidence-based guidelines".…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…60,61,68,71,79,81,94 This was attributed to improved attendance, greater accessibility, and decreased environmental impact. Of the remaining publications, 3 of 12 did not specifically ask the participants about format preference, although respondents indicated that they had enjoyed the conference and were willing to continue meeting virtually; 42, 89,96 1 of 12 reported a majority preference for in-person meetings; 44 and the final study reported approximately equal preference for in-person and hybrid/virtual. 82 Some studies attempted to evaluate conference impact using objective metrics -such as examining links between attendance and performance on the American Board of Emergency Medicine In-Training Examination and U.S. Medical Licensing Examination, 39 or distributing case study questionnaires to conference participants and non-participants to determine "whether the diagnostic and therapeutic choices of program participants were consistent with evidence-based guidelines".…”
Section: Discussionmentioning
confidence: 99%
“… 60 , 61 , 68 , 71 , 79 , 81 , 94 This was attributed to improved attendance, greater accessibility, and decreased environmental impact. Of the remaining publications, 3 of 12 did not specifically ask the participants about format preference, although respondents indicated that they had enjoyed the conference and were willing to continue meeting virtually; 42 , 89 , 96 1 of 12 reported a majority preference for in-person meetings; 44 and the final study reported approximately equal preference for in-person and hybrid/virtual. 82 …”
Section: Discussionmentioning
confidence: 99%